Art and Gender in School: A Study on the Teaching of Visual Arts from a Feminist Perspective - Ferreira, Alana de Oliveira (Revista do Colóquio, 2025)
This research reflects on gender issues within the school curriculum and how the teaching of visual arts can contribute to this discussion. Initially, it investigates the introduction of the topic of Sexual Orientation in the National Curriculum Parameters and the basis for discussing gender in the classroom. Next, it presents the feminist critique of art history, analyzing how this historiography was constructed around a masculine ideal, and how we should approach the discipline without perpetuating the same problems. Finally, it presents the importance of addressing these issues in visual arts classes and ways to do so.
Keywords: national curriculum parameters; gender; visual arts; feminism